2004
DOI: 10.4049/jimmunol.172.2.989
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Inhibition of CD8+ T Cell Response by Immature Myeloid Cells in Cancer Is Mediated by Reactive Oxygen Species

Abstract: Tumor growth is associated with the accumulation of immature myeloid cells (ImC), which in mice are characterized by the expression of Gr-1 and CD11b markers. These cells suppress Ag-specific CD8+ T cells via direct cell-cell contact. However, the mechanism of immunosuppressive activity of tumor-derived ImC remains unclear. In this study we analyzed the function of ImC isolated from tumor-free control and tumor-bearing mice. Only ImC isolated from tumor-bearing mice, not those from their control counterparts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
618
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 761 publications
(646 citation statements)
references
References 42 publications
22
618
2
4
Order By: Relevance
“…ROS production disrupts TCR signaling and it has been reported that reducing ROS releases CD8 T cell suppression by MDSC. 42 This mechanism appears to underlie the effects of RT/IL-12 on MDSC-mediated T cell suppression, as ROS production from tumor-infiltrating MDSCs only decreased when the tumor was treated with RT in combination with IL-12, but not with RT or with IL-12 alone (Figure 7(b,c). Another potential effect of combination therapy on MDSCs is to promote their further differentiation towards macrophages and DCs, as observed in TLR-7/8 agonist-stimulated MDSCs.…”
Section: Discussionmentioning
confidence: 96%
“…ROS production disrupts TCR signaling and it has been reported that reducing ROS releases CD8 T cell suppression by MDSC. 42 This mechanism appears to underlie the effects of RT/IL-12 on MDSC-mediated T cell suppression, as ROS production from tumor-infiltrating MDSCs only decreased when the tumor was treated with RT in combination with IL-12, but not with RT or with IL-12 alone (Figure 7(b,c). Another potential effect of combination therapy on MDSCs is to promote their further differentiation towards macrophages and DCs, as observed in TLR-7/8 agonist-stimulated MDSCs.…”
Section: Discussionmentioning
confidence: 96%
“…T cells further increase the activity of neutrophils through secretion of IFNγ. The increase in oxygen radicals have additional effects, such as suppression of T cell responses [278,384], activation of TGFβ [81], and induction of GMP-140 (P-Selectin) expression on the surface of endothelial cells, leading to enhanced neutrophil adherence and activity [385]. The activation of TGFβ suppresses excessive neutrophil function, and may polarize them into N2 neutrophils [13].…”
Section: Concluding Remarks -The Dialogue Between Cancer Cells and Nementioning
confidence: 99%
“…Gr-1 ϩ IMC freshly isolated from spleen of tumor-bearing mice could not inhibit CD4-mediated T cell response, but were able to suppress CD8 ϩ T cells in Ag-dependent manner (16). This inhibition required direct cell-cell contact and was mediated by reactive oxygen species (19). Interestingly, when Gr-1 ϩ cells were incubated for several days in vitro, they acquired ability to block CD4-mediated T cell responses (20).…”
Section: Stat1 Signaling Regulates Tumor-associated Macrophage-mediatmentioning
confidence: 99%